汉越鸟类名称构词法对比研究 - Nguyễn, Thị Hảo (NHÀ XUẤT BẢN ĐẠI HỌC QUỐC GIA HÀ NỘI, 2019)
在自然界，鸟类是所有脊椎动物中外形最美丽、声音最悦耳、深受人们喜爱 的一类动物。汉越两种语言都有大量鸟类名称。中国和越南山水相连，汉语和越南 语之间具有一种特别密切的关系。但同时，两种语言也呈现出鲜明的个性特征。其 中之一体现在鸟类名称构词法方面上。本研究在考察665个汉语鸟类名称和336个越 南语鸟类名称构词法的基础上，发现无论是汉语还是越南语，合成词名称数量都占 绝大多数的,其中，偏正式名称在两种语言中都占上风。因此，可以得出汉语鸟类 名称典型的构造形式为“区别语素+类属语素”，越南语鸟类名称典型的构造形式为“ 类属语素+区别语素”。此外，越南语单音节鸟类名称的比例接近汉语的两倍。原因 在于越南语的复音化趋势没有汉语那么强烈，而且越南语从汉语借来的词相当多。 In nature, birds are the most beautiful, sweetest and most beloved of all vertebrates. Both Chinese and Vietnamese languages have a large number of bird names. China and Vietnam are linked by mountains and rivers, and there is a particularly close relationship between Chinese and Vietnamese. However, at the same time, two languages also present a distinct personality characteristics and reﬂect on the name of the birds. Based on the survey of the names of 665 Chinese birds and 336 Vietnamese birds, this research analyzes and compares the similarities and diﬀerences between the formation of bird names in two languages. These names are mostly formed by compounding method. The typical construction form of Chinese bird names is “diﬀerential morpheme + classifed morpheme” whereas the typical construction form of Vietnamese bird names is “classifed morpheme + diﬀerential morpheme”. In addition, monosyllabic bird names in Vietnamese are nearly twice that of Chinese. The reason is that the polyphonic trend in Vietnamese is not as strong as Chinese, and there are a lot of words borrowed from Chinese.